2015
DOI: 10.1021/jo502841u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)-Aureol by Bioinspired Rearrangements

Abstract: A bioinspired and sustainable procedure for the straightforward synthesis of (±)-aureol has been achieved in eight steps (14% overall yield) from epoxyfarnesol. The key steps are the titanocene(III)-catalyzed radical cascade cyclization of an epoxyfarnesol derivative and a biosynthetically inspired sequence of 1,2-hydride and methyl shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 27 publications
2
32
0
1
Order By: Relevance
“…Physical and spectroscopic properties of synthetic (±)-aureol ((±)-1) matched those previously reported for the natural compound [2]. Thus, the synthesis of (±)-aureol ((±)-1) from (±)-albicanol (5) was completed in only seven steps and a global 28% yield, substantially improving the synthetic procedures previously published [11][12][13][14][15][16][17][18][19][20]. Moreover, a simple epimerization of aureol (1) to 5-epi-aureol (11) has The synthesis of (±)-aureol ((±)-1) (Scheme 2) used as starting material (±)-albicanol (5), which was prepared through Cp 2 TiCl-catalyzed radical cascade cyclization of epoxy-farnesyl acetate, as previously reported by us and others [24,25].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Physical and spectroscopic properties of synthetic (±)-aureol ((±)-1) matched those previously reported for the natural compound [2]. Thus, the synthesis of (±)-aureol ((±)-1) from (±)-albicanol (5) was completed in only seven steps and a global 28% yield, substantially improving the synthetic procedures previously published [11][12][13][14][15][16][17][18][19][20]. Moreover, a simple epimerization of aureol (1) to 5-epi-aureol (11) has The synthesis of (±)-aureol ((±)-1) (Scheme 2) used as starting material (±)-albicanol (5), which was prepared through Cp 2 TiCl-catalyzed radical cascade cyclization of epoxy-farnesyl acetate, as previously reported by us and others [24,25].…”
Section: Resultssupporting
confidence: 64%
“…As a continuation of our research on the synthesis of marine natural bioactive compounds [18,[21][22][23], we have developed a new concise route for the synthesis of tetracyclic meroterpenoids. In this new synthetic route, aureol (1) is the key intermediate from which other tetracyclic meroterpenoids, such as 2, 3 and 4, can be easily synthesized by simple functional modification of its aromatic ring.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these approaches, in which the crucial stereochemistry of the decalin ring system is set in a stepwise manner, Rosales applied a very elegant Ti III ‐mediated reductive epoxide cyclization cascade to construct 11 . In addition, Cramer reported a ruthenium(III)‐catalyzed domino cyclization of a model substrate to access the tetracyclic core of the aureol family of natural products …”
Section: Introductionmentioning
confidence: 99%
“…As previous work has shown that formation of the tetracyclic ring system via biomimetic polyene cyclization and Wagner–Meerwein shifts can only occur in a stepwise manner in the laboratory, we were searching for a strategy to mimic the highly organized environment of an enzymatic active site more efficiently. In order to overcome the current inability of synthetic methodology to mimic these two independently occurring events in a single flask, we recently investigated the cyclization of a well‐elaborated polyene .…”
Section: Introductionmentioning
confidence: 99%
“…A concise synthesis of 5,6-dibromotryptamine has been accomplished, starting from the intermediate 5,6-dibromoindole-3-carbaldehyde [ 89 ]. First synthesis of the chiral paureol had been described before, starting from (+)-arenarol [ 90 ], while other syntheses have been recently reported [ 91 , 92 ].…”
Section: Porifera Involved In the Biosynthesis Of Cytotoxic Metabomentioning
confidence: 99%